Peningkatan Hasil Belajar Kognitif Siswa Melalui Model Pembelajaran Kontekstual Pada Materi Perkalian dan Pembagian - Olenggius Jiran Dores; Yakobus Bustami; Rupina Mila Maria Ana (IKIP Mataram, 2019)
The Enhancement of Students' Cognitive Learning Achievement Through Contextual Learning Model on Multiplication and Division’s Matter. This research was based on the number of students who produce the resuits of cognitive learning under minimal mastery. The purpose of this research was to improve student cognitive learning outcomes and improve the learning process by applying the contextual learning model. The approach used in this research was descritptive qualitative approach with classroom action research method consisting of two cyeles. Subjects in this researchwere the students of elementary school classs III 48 Lepung Beruang were 43 students who taught by the modeling of contextstual. The instrument for measuring cognitive learning outcomes. The data obtained were analyzed by using desctiptive whit mean and Classical completeness value. The result of descriptive analysis shows that in cycle I, the result of 29 students is complete with an average of 66,00 and classical completeness of 67,44%. Furthermore, in cycle II, students who complete 37 students with average of 78,60 and classical completeness of 86,04% of students into good category. The results of this study can be concluded tahat the modeling of use can improve student learning outcomes on mathematic materials.Based on, the result of the teacher activity observation has been received 60% the first meeting, 65% the second meeting on the first cycle, meanwhile on the second cycle at the first meeting has got constantly becoming increasing 100%. The results of this research can be concluded that the use of contextual learning can improve the cognitive learning outcomes of students in multiplication and division material and improve the learning process of learning